Romania : 2021 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Among EU countries, Romania suffered a relatively shallow recession in the COVID-19 crisis, aided by macroeconomic easing. A strong recovery is projected in 2021. The new government is committed to balance continued pandemic-related support with the start of a medium-term fiscal consolidation trajectory that corrects pre-pandemic excesses, while implementing a range of structural reforms. These efforts, as well as the medium-term recovery, should be bolstered by large Next Generation EU grants.